Talang Indah As the Potential Tourism Place: The Natural Talang Air Pringsewu and Historic Tourism in Pringsewu Regency - Tristiana, Novita Eka; Izhar (Research and Social Study Institute, 2022)
Talang Indah as the tourism icon in Pringsewu Regency has great potential which full of historical. This needs great attention from the government, society and also the tourism activator. Talang Indah is located in a strategic place that is in the middle of Pringsewu district exactly in Fajaresuk. Formerly, Talang Indah is the favorite location place for Pringsewu society, but since pandemic era, this place is not well operated. This training uses a project-based learning approach with three stages of activity. At the first step the trainers presented the steps how to design the poster, banner, booklet by using Canva. After that, the participants directly practicing to design the poster by using Canva. The last step, the best design was published in Instagram and Facebook belong to Talang Indah Pringsewu The digital marketing chosen is creating the promotion media by using CANVA application. This APP was chosen because this is easy and effective. There are 11 participants in on day training. The result is the promotion staff are able to create the digital marketing media by using CANVA.